1997
DOI: 10.1007/s004310050588
|View full text |Cite
|
Sign up to set email alerts
|

The impact of surfactant replacement therapy on cerebral and systemic circulation and lung function

Abstract: In RDS patients there is a significant drop of MAP, HR, MCBFV and FiO2 after bolus surfactant administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 9 publications
1
20
0
1
Order By: Relevance
“…Most of these studies demonstrated significant changes in blood pressure and CBFV within 5 minutes after surfactant administration and then returned to baseline levels within 20 to 30 minutes. [7][8][9][10][11] In human newborn infants, there are only two studies 12,13 using synthetic surfactant (colfoceril palmitate) (Exosurf; Glaxo Wellcome, Research Triange Park, NC), and these studies showed conflicting results with regard to CBFV changes. There is only one study using bovine natural surfactant that showed no significant changes in CBFV with surfactant administration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of these studies demonstrated significant changes in blood pressure and CBFV within 5 minutes after surfactant administration and then returned to baseline levels within 20 to 30 minutes. [7][8][9][10][11] In human newborn infants, there are only two studies 12,13 using synthetic surfactant (colfoceril palmitate) (Exosurf; Glaxo Wellcome, Research Triange Park, NC), and these studies showed conflicting results with regard to CBFV changes. There is only one study using bovine natural surfactant that showed no significant changes in CBFV with surfactant administration.…”
Section: Discussionmentioning
confidence: 99%
“…Both variables were included because they have been reported to have an effect on CBFV and blood pressure. 4 -6 Furthermore, an increase in PACO 2 has been reported with surfactant administration in various studies, [7][8][9][10][11][12][13] and associated changes in CBFV were explained by PACO 2 changes. 12 The software used for statistical analysis was the S-Plus statistics package (Mathsoft, Seattle, WA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many respiratory problems or treatments are known to alter cerebral blood flow and/or increase the risk of intraventricular haemorrhage. These include:  intratracheal surfactant instillation (has been shown to increase or decrease cerebral blood flow velocity on Doppler ultrasound (Schipper, 1997;Saliba, 1994;Kaiser, 2004);  asynchronous breathing mechanical ventilation (increases the variability of cerebral blood flow (Rennie, 1987);  endotracheal tube suction (has been shown to increase or decrease cerebral blood flow on near infrared spectroscopy (Limperopoulos, 2008;Kohlhauser, 2000);  endotracheal tube retaping increases cerebral blood flow on near infrared spectroscopy (Limperopoulos, 2008);  pneumothorax increases cerebral blood flow velocity on Doppler ultrasound, and increases the incidence of intraventricular haemorrhage. Mehrabani, 1991) The alterations in cerebral blood flow during the administration surfactant are of particular concern because surfactant administration is comparable to the intratracheal administration of perfluorocarbon when starting partial liquid ventilation.…”
Section: The Risk Of Brain Injury In the Extremely Preterm Infantmentioning
confidence: 99%
“…Many respiratory problems or treatments are known to alter cerebral blood flow and/or increase the risk of intraventricular haemorrhage. These include:  intratracheal surfactant instillation (has been shown to increase or decrease cerebral blood flow velocity on Doppler ultrasound (Schipper, 1997;Kaiser, 2004);  asynchronous breathing mechanical ventilation (increases the variability of cerebral blood flow (Rennie, 1987);  endotracheal tube suction (has been shown to increase or decrease cerebral blood flow on near infrared spectroscopy (Limperopoulos, 2008;Kohlhauser, 2000);  endotracheal tube retaping increases cerebral blood flow on near infrared spectroscopy (Limperopoulos, 2008);  pneumothorax increases cerebral blood flow velocity on Doppler ultrasound, and increases the incidence of intraventricular haemorrhage. Mehrabani, 1991) The alterations in cerebral blood flow during the administration surfactant are of particular concern because surfactant administration is comparable to the intratracheal administration of perfluorocarbon when starting partial liquid ventilation.…”
Section: The Risk Of Brain Injury In the Extremely Preterm Infantmentioning
confidence: 99%